Reservation strategy to increase room occupancy through online platform at Desa Visesa Ubud Resortt - Desak Koming Sundari; Ni Nyoman Triyuni; I Gusti Made Wendri (Politeknik Negeri Bali, 2020)
Purpose: This study aims to determine the contribution of online platforms to room occupancy rates in 2017 to 2019 and to find out reservation strategies in increasing room occupancy through online platforms in Desa Visesa Ubud Resort. Research methods: The data used in this study were collected by interview, observation, documentation, and literature study methods which are then processed using descriptive statistical analysis techniques and qualitative descriptive techniques using Excel tools to analyze data. Results and discussion: The percentage of the contribution of the five online platforms that collaborate with Desa Visesa Ubud Resort namely Agoda, Booking.com, Expedia, Tiket.com, and Waka showed a number of more than 50% which could be interpreted that the online platform contribution was very significant for occupancy rooms at Desa Visesa Ubud Resort in 2017-2019. Conclusion: In increasing room occupancy in Desa Visesa Ubud Resort, all reservation staff use marketing strategies and balance with good personality attributes in an effort to improve room occupancy, especially in increasing room occupancy through the online platform. It is recommended that sales and marketing can evaluate each online platform and for management to add other strategies, especially strategies in marketing the rooms so that room occupancy can increase